Evidence-Based Review of Nonsurgical Management of Colorectal Cancer Liver Metastasis and Evolving Role of Interventional Radiology - Wu, Hanping; Opneja, Aman; Sutter, Christopher; Patel, Indravadan; Lewandowski, Robert J.; Eads, Jennifer; Tavri, Sidhartha (Digestive Disease Interventions, 2017)
Colorectal cancer is the third most common malignancy and the second leading cause of cancer death in the United States. Approximately 20 to 25% of patients have clinically detectable colorectal liver metastases (CLM) at the initial diagnosis, and nearly 50% of patients with colorectal cancer develop hepatic metastases at some point during the course of their disease. Patients with untreated CLM have a median survival time of approximately 4.5 months. For the resectable cases, surgical resection is the first-choice treatment. However, only 10 to 30% of patients with CLM are eligible for resection at presentation. There are several nonsurgical treatment options for patients with CLM who are not candidates for initial or potentially curative resection. These include systemic chemotherapy, locoregional therapy that includes thermal and nonthermal ablation, external beam radiation therapy, regional chemotherapy via the hepatic artery, and selective radioembolization using yttrium-labeled glass or resin microspheres. In this review, we discuss the nonsurgical treatment options described earlier that are part of the current multidisciplinary algorithm in the management of CLM and focus on the expanding role of interventional radiology.
Keywords: colorectal cancer; liver metastases; nonsurgical management